PERSEPSI GURU TENTANG PROSES PELAKSANAAN SUPERVISI PEMBELAJARAN OLEH KEPALA SEKOLAH MENENGAH KEJURUAN NEGERI KELOMPOK BISNIS MANAJEMEN DI KOTA PADANG - Rezy Marsellina (Jurnal Bahana Manajemen Pendidikan, 2014)
The purpose of this study was to obtain information about Perception Learns about Performing Process Supervise Learning by vocational Middle School head Business agglomerate Country Management at Moorland City  in planning instructional supervision, implementation of instructional supervision, and evaluation of the implementation of instructional supervision. The study population was a teacher vocational high school business management group in the city of Padang as 123 people. The number of samples is 54 people who were taken using Proportional Stratified Random Sampling technique. Means of collecting data in this study is a questionnaire, Likert Scale models that have been tested for validity and reliability; and the results are valid and reliable. Data analysis techniques using the average score. The result from this study about the perceptions of teachers toward instructional supervision by the head of the Business Management Group at SMKN Padang is enough performed. Key word: Implementation, Instructional Supervision, The Principal